Calculation of energy deposited and stopping range through deuterium ignition beam and dynamical studies on the energy gain in D-3He mixtures - S. N. HOSSEİNİMOTLAGH; M. JAHEDİ; S. KİANAFRAZ; Sakineh GHADERİ (International Journal of Applied Methods in Electronics and Computers, 2015)
The fast ignition approach to ICF consists in ﬁrst compressing the fuel to high density by a suitable driver and then creating the hot spot required for ignition by means of a second external pulse. If the ignition beam is composed of deuterons, an additional energy is delivered to the target with increased energy gain. Therefore ,in this innovative suggestion ,we consider deuterium  beams for fast ignition in D+ 3 He mixture and solve the dynamical  balance equations under the available  physical conditions by considering a new average reactivity formula ,then we compute the energy gain in this mixture .Our computational results show that we can get energy gain value larger than 1000 at resonant temperature (380keV)of D+ 3 He  mixture. We select D+ 3 He fuel, because D+ 3 He reaction is very attractive from a theoretical point of view since it does not produced neutrons. The D+ 3 He benefits include full-lifetime materials, reduced radiation damage, less activation, absence of tritium breeding blankets, highly efficient direct energy conversion, easier maintenance, proliferation resistance. The deposited energy can reduce laser driver energy. Our calculations show that at 380 Kev (resonant temperature) the maximum numbers of fusion reactions are performed and the energy gain is maximized.